DISKRIMINASI HUKUM DALAM PEMBERANTASAN KORUPSI POLITIK DI DAERAH - Jupri Jupri; Roy Marthen Moonti (Faculty of Law, Maranatha Christian University, 2019)
Corruption is an act to against the law and moral because it is considered as an act abusing the power and authority for personal’s benefit, group or other parties to take advantage each other either economically or politically. Due to perpetrators of corruption is a public official, the type of corruption is considered as political corruption. One of many cases of political corruption in regional level is corruption on social assistance fund. The reality of social assistance fund corruption case disclosure in many regionals seems difficult. The sociology aspect takes a part in law enforcement such as stratification, morphology and intervention variables. Stratification which is a formal position of somebody, friendship between law enforcers and the suspect, and intervention of superior to the subordinate in legal institution confirm the legal discrimination in corruption act of social assistance fund. Therefore, to suppress the rate of corrupt behavior in regional level, it needs the legal enforcement reconstruction started from legal enforcer side to the encouragement of legal enforcer reformation in regional level. The legal enforcer reformation should emphasize on the importance of rolling job system at the top management in the legal enforcement institution. This system can enrich experience and perception, and to sharpen the skills. On the other hand, it can minimize the occurrence of morphology aspect between the legal enforcer and local elites. Besides, the involvement of justice collaborator in corruption eradication should be implemented in order to reveal the political corruption case which is complicated and neatly covered.